HIV-Associated TB Syndemic: A Growing Clinical Challenge Worldwide - Montales, Maria Theresa; Chaudhury, Arun; Beebe, Alexandria; Patil, Sowmya; Patil, Naveen (Frontiers in Public Health, 2015)
The association of tuberculosis (TB) with human immunodeficiency virus (HIV) infection and acquired immune deficiency syndrome (AIDS) over the past several years has become an emerging syndemic. Approximately 10% of people living with HIV (PLHIV) with latent TB infection will develop active TB disease each year. In this review, we highlight that this phenomenon is not limited to high endemic regions like Afro-Asian nations, but globalization/migration is causing increased case detection even in developed nations such as the United States (US). Active screening should be performed for tuberculosis in PLHIV. A high degree of clinical suspicion for tuberculosis is warranted in PLHIV presenting with fever, cough and unintentional weight loss. HIV-Mycobacterium tuberculosis (MTB) coinfection is often paucibacillary, precluding diagnosis by conventional diagnostics and/or smear-microscopy/culture. Improved detection of pulmonary and extrapulmonary tuberculosis is now possible by incorporation of the GeneXPERT MTB/RIF assay (Cepheid Inc, Sunnyvale, USA). The World Health Organization (WHO) recommends instituting immediate therapy for Mycobacterium tuberculosis, in conjunction with ongoing or newly introduced antiretroviral therapy (ART). Vigilance is required to detect drug-induced organ injuries, and early-treatment induced immune reconstitution inflammatory syndrome (IRIS). Collaborating MTB and HIV activities in concentrated HIV epidemic settings should become a high public health priority.